1985
DOI: 10.1017/s0272263100005568
|View full text |Cite
|
Sign up to set email alerts
|

Students Learn Language via a Civilization Course—A Comparison of Second Language Classroom Environments

Abstract: The primary goal of this research was to compare the improvement in the second language skills of listening, speaking, reading, and writing among fourth semester French students enrolled in a content course taught in French and similar level students enrolled in a traditional fourth semester French course where the focus was primarily on the teaching of the language itself. The research used a non-equivalent pretest-posttest design and the results were analyzed using an analysis of covariance to determine mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…Results from TB programs are similar in nature to those just presented for SLM. Several studies report that students in experimental classes made significant pre-and post-gains on a variety of language measures (Corin 1997;Klahn 1997;Klee and Tedick 1997;McQuillan 1996;McQuillan and Rodrigo;Milk 1990;Peck 1987;Rodrigo 1997;Stryker 1997; see Table 2 for results) and scored comparably or significantly higher than students enrolled in skill-based courses at the same level, even though there was no explicit grammar or other language instruction (Chadran and Esarey 1997;Dupuy 1996;Hudson 1991;Kasper 1997;Lafayette and Buscaglia 1985;Leaver 1997;Schleppegrell 1984;Sternfeld 1992Sternfeld , 1993; see Table 2 for results).…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from TB programs are similar in nature to those just presented for SLM. Several studies report that students in experimental classes made significant pre-and post-gains on a variety of language measures (Corin 1997;Klahn 1997;Klee and Tedick 1997;McQuillan 1996;McQuillan and Rodrigo;Milk 1990;Peck 1987;Rodrigo 1997;Stryker 1997; see Table 2 for results) and scored comparably or significantly higher than students enrolled in skill-based courses at the same level, even though there was no explicit grammar or other language instruction (Chadran and Esarey 1997;Dupuy 1996;Hudson 1991;Kasper 1997;Lafayette and Buscaglia 1985;Leaver 1997;Schleppegrell 1984;Sternfeld 1992Sternfeld , 1993; see Table 2 for results).…”
Section: Research Findingsmentioning
confidence: 99%
“…In a university context, where academic budgets are generally tight, bureaucratic levels are numerous, disciplinary turf battles are fierce, and research and publication are rewarded over teaching and advising, models such as SLM, AL, or FLAC may not be the easiest or fastest way to provide CBI in a foreign language. The TB model, however, is more flexible, less costly, less labor intensive, and somewhat simpler to implement that the other approaches, because it can be easily integrated within existing language courses6 and tailored to meet the variety of competence levels: Beginning (Corin 1997;Leaver 1997;Sternfeld 1992Sternfeld , 1993Sternfeld , 1997; Intermediate (Klee and Tedick 1997;Lafayette and Buscaglia 1985;Vines 1997), andAdvanced (Chadran andEsarey 1997;Klahn 1997;Stryker 1997). SLM courses at the university level require at least an intermediate level of competence (Burger 1989;Edwards et al 1985;Hauptman et al 1988) so that students can handle the material and take full advantage of the sheltered strategies, thus furthering their acquisition of the L2 and learning the subject matter.…”
Section: Achieving Cbis Potential Benefitsmentioning
confidence: 99%
“…Different research studies have shown that formal grammar instruction can: (a) have no apparent effect on language acquisition (Carroll, 1964;d'Anglejan, 1978;Dulay & Burt, 1973;Harley, 1989;Perkins & Larsen Freeman, 1975; The Modern Languugz Journal, 79, iii (1995) "1995 The Modern Languagz Journal 0026-7902/95/329-355 $l.50/0 Saegert, Scott, Perkins, & Tucker, 1974); (b) be unnecessary for language acquisition (Edwards, Wesche, Krashen, Clement, & Kruidenier, 1984;Hammond, 1988;Lafayette & Buscaglia, 1985;Terrell, Gomez, & Mariscal, 1980); (c) have positive effects on language acquisition (Doughty, 1991;Eckman, Bell, & Nelson, 1988;Harley, 1989;Hulstijn & Hulstijn, 1984;Long, 19831;Pica, 1983;Pienemann, 1989;VanPatten & Cadierno, 1993); (d) have detrimental effects on language acquisition (Pienemann, 1989); and (e) (when absent) have negative effects on language acquisition (Higgs & Clifford, 1982). Similar contradictions appear in research on error correction.…”
mentioning
confidence: 99%
“…In some cases, the TL is the medium of instruction and mastery of the content is crucial (Met 1994, 1999; Genesee 1994 at: http://www.ncbe.gwu.edu/miscpubs/ncrcdsll/epr11.htm; Cummins 2000 at: http://www.iteachilearn.com/cummins/immersion2000.html). In others, the content is a vehicle for enhancing TL mastery but subordinate as an outcome (Lafayette and Buscaglia 1982; Stryker and Leaver 1997; Pessoa et al. 2007; Grim 2008).…”
Section: Curriculum Developments: the Search For A Communicative Syllmentioning
confidence: 99%
“…html). In others, the content is a vehicle for enhancing TL mastery but subordinate as an outcome (Lafayette and Buscaglia 1982;Stryker and Leaver 1997;Pessoa et al 2007;Grim 2008). In yet others, the position is more balanced (Shaw 1997; and for a valuable survey and examples, see the CoBalTT website at: http://www.carla.umn.edu/cobaltt/ modules.html).…”
Section: Curriculum Developments: the Search For A Communicative Syllmentioning
confidence: 99%